1983
DOI: 10.1002/pssa.2210750219
|View full text |Cite
|
Sign up to set email alerts
|

ZnSe:Mn in AC thin film electroluminescence devices

Abstract: The properties of ac driven thin film devices using ZnSe:Mn instead of ZnS:Mn as semiconductor layer are assessed. The principal advantage of low threshold is offset by inherent inefficiency of the temperature quenched Mn2+‐emission in ZnSe. No hysteretic behaviour could be obtained in structures otherwise identical to hysteretic ZnS ac TFDs. A rather interesting inversion in runaway and carrier injection thresholds for ZnSe relative to ZnS devices can be supposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…In Ref. [25] it was reported that the EL intensity of the ZnSe:Mn device was substantially lower than that of ZnS:Mn, but in Ref. [8] increased luminance of the ZnS 1Àx Se x :Mn devices were reported as a consequence of band gap engineering by addition of Se.…”
Section: Article In Pressmentioning
confidence: 96%
See 1 more Smart Citation
“…In Ref. [25] it was reported that the EL intensity of the ZnSe:Mn device was substantially lower than that of ZnS:Mn, but in Ref. [8] increased luminance of the ZnS 1Àx Se x :Mn devices were reported as a consequence of band gap engineering by addition of Se.…”
Section: Article In Pressmentioning
confidence: 96%
“…Earlier EL studies on ZnS 1Àx Se x :Mn and ZnSe:Mn thin films have shown that the emission color of Mn does not change due to the addition of Se [8,25]. In Ref.…”
Section: Article In Pressmentioning
confidence: 98%